The APP : Assessment of Physiotherapy Practice Instrument : clinical educator resource manual. - Dalton, Megan; Keating, Jennifer L.; Davidson, Megan (Australian Learning and Teaching Council, 2009)
Clinical educator's guide to using the Assessment of Physiotherapy Practice Instrument (APP). a standardised instrument to assess clinical performance of Australian physiotherapy students. An assessment instrument was required to meet the needs of students and educators and provide valid and reliable measurements of clinical competence. The guide covers aspects such as: assessing clinical units; assessing physiotherapy practice; challenges in assessment; challenges in scoring; assessment myths; hints for achieving best practice; ensuring consistency in assessment; and use of the DVD for training in assessment.